The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/bf02736704
|View full text |Cite
|
Sign up to set email alerts
|

Transapical aortic cannulation using a deep hypothermic procedure through a left thoracotomy for acute traumatic aortic rupture

Abstract: We describe a transapical aortic cannulation procedure through a left thoracotomy for a case of acute traumatic aortic rupture. A 26-year-old man was involved in a motor vehicle accident and admitted in a state of hypovolemic shock. Chest computed tomography findings revealed a rupture of the proximal portion of the descending aorta and a massive hematoma around the aorta extending into the thoracic cavity. Under hypothermic circulatory arrest, he underwent an emergency graft replacement through a left thoraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Shiiya et al 4 reported a case of thoracoabdominal aortic repair with apical cannulation and stated that apical cannulation was advantageous in terms of preventing retrograde thrombotic events. Takemura et al 5 reported the usefulness of transapical cannulation to prevent malperfusion in the treatment of an acute traumatic descending aortic rupture. The advantages of transapical cannulation include antegrade perfusion, true lumen perfusion, and quick establishment of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Shiiya et al 4 reported a case of thoracoabdominal aortic repair with apical cannulation and stated that apical cannulation was advantageous in terms of preventing retrograde thrombotic events. Takemura et al 5 reported the usefulness of transapical cannulation to prevent malperfusion in the treatment of an acute traumatic descending aortic rupture. The advantages of transapical cannulation include antegrade perfusion, true lumen perfusion, and quick establishment of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…The ascending aorta and thoracic descending aorta are frequently selected as the cannulation route for perfusing the upper body, but this route is not appropriate in patients with profound atherosclerotic changes, such as a shaggy and calcified aorta [9]. Shiiya et al reported using antegrade perfusion by transapical aortic cannulation to prevent debris scattering due to retrograde perfusion from the femoral artery in a patient undergoing thoracoabdominal aortic repair by left thoracotomy [7], and Takemura et al reported the usefulness of transapical cannulation in preventing malperfusion during a deep hypothermic procedure to repair an acute traumatic descending aortic rupture [10]. Although antegrade perfusion via the axillary artery is safe and possible [11], it is difficult to ensure the visual field during a left thoracotomy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Shiiya et al4 reported a case of thoracoabdominal aortic repair with apical cannulation and stated that apical cannulation was advantageous in terms of preventing retrograde thrombotic events. Takemura et al5 reported the usefulness of transapical cannulation to prevent malperfusion in the treatment of an acute traumatic descending aortic rupture. The advantages of transapical cannulation include antegrade perfusion, true lumen perfusion, and quick establishment of CPB 6.…”
mentioning
confidence: 99%